(untitled) (Khairulummah, 2022)
The main purpose of this research is to make known the historical information presented by orientalist William Montgomery Watt in his book “A Short History of Islam”, which aims to present his own conceptions and the conclusion of his experience in the study of Islam and its history and beliefs as a Western reader. This study is based on some of the precautions of this Orientalist regarding the biography of the Prophet Muhammad (peace and blessings of Allah be upon him), showing them and criticizing them in case .And respond to them on the statement of validity of falsity. Here, it should be emphasized that, it is too hard to recognize the validity of what Orientalists have written, Especially those who have been interested in writing about the history of the Muslims, their culture and their faith, as the most common orientalists were their aim was to distort, slander the Misrepresentation of historical facts and events. The few who are committed to the rules of equitable scientific research, and these have been fair Muslims and their history and weighed the events and facts, balance justice and equity.